(untitled) (Journal of Scientific Research, 2017)
Petroleum ether (Pet. ether), CHCl3 and CH3OH extracts of white mulberry were subjected to dose-mortality tests against Callosobruchus chinensis (L.), Sitophilus oryzae (L.) and Tribolium castaneum (Hbst.). Pet. ether extract of leaves against C. chinensis, S. oryzae and T. castaneum provided LD50 9.16, 5.06, 3.79, 2.81, 2.06, 1.55, 1.32, 1.38 mg/g; 17.6, 12.9, 11.3, 82.4, 83.5, 9.47, 8.73, 8.61 mg/g and 0.93, 0.826, 0.691, 0.623, 0.567, 0.532, 0.525 mg/cm2 after 0.5, 6, 12, 24, 36, 48, 60, 72 h of exposures respectively. Against C. chinensis Pet. ether extract of root and stem bark gave LD50 28.3, 20.7, 18.4, 16.9, 14.4, 13.6, 13.3, 13.3 mg/g and 86.3, 228.9, 177, 109, 61.0, 21.8, 0.999, 15 mg/g after 0.5, 6, 12, 24, 36, 48, 60, 72 h of exposures respectively. CH3OH extracts of leaves offered LD50 21.5, 20.4, 17, 16.2, 15.6, 14.7 mg/g against C. chinensis; 5.4, 14.7, 13.7, 11, 10.9, 9.46, 9.10 mg/g against S. oryzae; and 3.804, 3.429, 3.284, 2.736, 2.441, 2.311, 2.264 mg/cm2 against T. castaneum after 6, 12, 24, 36, 48, 60, 72 h of exposures respectively. Against S. oryzae CH3OH extract of root and CHCl3 of stem bark gave LD50 19.5, 19.1, 17.5, 16.7, 16.2, 15.8, 15.9 mg/g and 9.77, 9.44, 7.71, 6.56, 5.94, 5.39, 5.4 mg/g after 6, 12, 24, 36, 48, 60, 72 h of exposures respectively. However, CHCl3 extract of leaves and root didnt show mortality.